Mathematical Identity in Learning Mathematics: Bibliometric Review - Muhamat Hidayatul Ridho; Ilham Muhammad; Endang Cahya Mulyaning A (Studies in Learning and Teaching, 2023)
Students' mathematical identities must be appropriately identified to obtain information on the causes of difficulties and decreased student motivation in learning mathematics so that this becomes a teacher's reference in preparing learning scenarios that can form strong and enduring mathematical characters in students. This bibliometric study aims to assess the global research trends in the field of mathematical identity by analyzing publication output, co-authorship among authors and their country affiliations, and the co-occurrence of author keywords. Using the Scopus database, a total of 53 journal articles published between 2007 and 2023 were collected. The findings indicate a consistent growth in the number of publications since 2018, with an increment of 5 articles every two years. Consequently, the cumulative total of articles has steadily increased. The United States stands out as the leading contributor, accounting for approximately 60% of the global publications, surpassing ten other countries/territories. Moreover, among the most productive universities in the top 5 countries, four of them are ranked in the top 1000 universities in the world. In conclusion, recent advancements in research on mathematical identity encompass various aspects such as mathematics achievement, race, equity, learners' mathematical identity, and black students.